Price Differentials in the U.K. Audit Services Market - Song, Yue (2009)
The purpose of this dissertation is to consider whether there are price differentials in the U.K. audit services market under different situations. The empirical studies cover four aspects: Big Four premium; price differentials among accounting firms with different sizes; audit fee differentials within Big Four; audit fee differentials between different industries.